Are Shared-Goal Congruence, Customer Relationship Management, and Customer Relationship Advantages Matter to Leverage Firm Performance? Indonesia Cases on Retail - Mahfudz Mahfudz; Kardison Lumban Batu; Aulia Vidya Almadanaa (Media Ekonomi dan Manajemen, 2025)
This study empirically investigates the relationship between shared-goal congruence, customer relationship management (CRM), and customer relationship advantages on firm performance. Data were collected from 200 supply chain practitioners and operations staff working in retail stores in Indonesia using purposive and non-probability sampling techniques. The hypotheses were assessed using SEM-AMOS 24, after conducting Exploratory Factor Analysis, reliability, and validity tests. The results show that CRM significantly impacts firm performance, mediated by Green Supply Chain Management (GSCM). Additionally, a positive relationship exists between goal congruency and firm performance, also mediated by GSCM. Supplier relationship management was found to have a significant effect on both GSCM and firm performance. The theoretical contribution of this study emphasizes that the integration of sustainable principles in supply chain management through GSCM improves firm performance in various aspects, including financial, environmental, and social. The implementation of GSCM, supported by strong management commitment and a shift in organizational culture, enhances energy and resource efficiency, process and product innovation, environmental risk reduction, customer satisfaction, continuous improvement, and cost reductions, leading to competitive advantages through faster and more accurate decision-making.